O educando com síndrome de down: um estudo sobre a relação entre pais e profissionais na escola regular - Muniz, Hiltnar Silva (2009)
This work makes a documental analise about the relationship between families of Down syndrome students and professionals of who teach them, in order to improve the process of developing teaching-learning, in an inclusive perspective. For this, we use a qualitative approach, because we believe that the object of research is not a passive and neutral knowledge, since it has meanings and relationships whose can be better interpreted and understood by the researcher in a real and active situation. For the development of this research, a bibliographical review was made about the subject, and a case studied in two regular education schools, both of them at the city of Natal/RN, one public and another one particular. We work on these educational institutions with professionals and parents of Down syndrome students. As an instrument of building information we used a semi-structured interview and to analise the results a qualitative method. Crossing the stages, we noticed: the pedagogical coordinators who made up both analyzed schools showed interest about doing an effective work with parents, regardless of Educational Policy Project of each school, predict or not the participation on educational undertaken process; On teachers discourses, reporting the relationship with the family, we realize that one of those teachers try to keep a good relationship with parents, permeated by learning exchanges, guidance and knowledge, in relation to another one, even existing an apparent openness to dialogue, when parents have any suggestions or criticism, that attitude is not always well coming. From the parents interviews, we can emphasize, first of all, that both of them recognize the benefits of inclusion, with regard to socialization - in general from the coexistence with pairs and the process of teaching and learning, as shown in a consistent way. Regarding school meetings with teachers, the studied parents agree about importance of such appointments and try to attend them, besides the other events organized by the school, beyond keeping individual touch with the teacher, when necessary. They are always present, looking for get envolved in everything that happens at school, in order to know better what is being done, listening and may suggest alternatives to improving the educational process. We perceive, from the study undertaken, that although the school inclusion is not an easy process to be built, is something that could be achieved. For this, is necessary that professionals of education and families recognize their functions in the educational process and act jointly on this direction